2006
DOI: 10.1191/1474474006eu354oa
|View full text |Cite
|
Sign up to set email alerts
|

A geography of big things

Abstract: This paper sketches some conceptual tools by which cultural geographers might advance geographies of architecture. It does so by thinking specifically about one architectural form: the modernist residential highrise, which is the ‘big thing’ of this paper. The paper draws on recent developments in material semiotics in order to interrogate features often uniquely associated with the highrise, such as its global reach, uniformity, and scale. The paper first rethinks how cultural geography has traditionally expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
244
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(252 citation statements)
references
References 14 publications
(16 reference statements)
0
244
0
8
Order By: Relevance
“…Emergence and becoming are two central concepts in this theory, indicating how different components are shaped in processes of interaction (DeLanda, 2006, 2016). The concept of assemblage has been applied to architecture in the sense that architecture is an assemblage formed by its included material, human and spatial components (Dovey, 2013; Jacobs, 2006). Assemblage theory endows dead material with agency.…”
Section: Introductionmentioning
confidence: 99%
“…Emergence and becoming are two central concepts in this theory, indicating how different components are shaped in processes of interaction (DeLanda, 2006, 2016). The concept of assemblage has been applied to architecture in the sense that architecture is an assemblage formed by its included material, human and spatial components (Dovey, 2013; Jacobs, 2006). Assemblage theory endows dead material with agency.…”
Section: Introductionmentioning
confidence: 99%
“…Third, Jane Jacobs' rich, subtle and innovative work on the Modernist high-rise has moved beyond purely semiotic and/or practice-based approaches (Jacobs 2006;Jacobs et al 2007). Her work accounts for the form-ing of artefacts that obtain coherence as buildings: in this case, "big" buildings.…”
Section: Narrating Architecture: De-centring Architectsmentioning
confidence: 99%
“…However, whilst writing this article, I found that it became increasingly difficult -and problematic -to articulate the kinds of traceable "relations" which inform geographical work on architecture and beyond (e.g., Jacobs 2006). I identify utopian designs, texts, practices and emotions whose relationship with one another is unclear; similarly, I suggest that there is at best an ambivalent relationship between diverse architectural movements around the HundertwasserHaus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations